STRATEGI PENGEMBANGAN HEALTH AND WELLNESSDI BALI - Pramono, Jaya (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 7 Nomor 1 Tahun 2013, 2013)
As a tourist destination, the name of Bali is popular having health and wellness tourism area, and in several times was known as one of the best spa destinations. The industry of health and wellness in Bali hasbeen become a part of tourism Department, and it need strategy for development in accordance to face theregional and world competition. This paper tried to describe the development strategy of Bali as a destination of health and Wellness tourism, which covers ten aspects to be need performed. The ten aspects are included; Find Yourself within the Global Marketplace, Position Yourself within the subregion, Identify Your Product and/or Service Offering , Identify Your Target, Prepare to Overcome Potential Barriers, Know What Your Competitors Are Doing, Differentiate Yourself from the Competition, Pursue Opportunities to Partner, Employ a Promotion Strategy.
Keywords: bali; tourism; health and wellness (Spa Industry)